2002
DOI: 10.1046/j.1462-2920.2002.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the action of aromatic effectors on the prokaryotic enhancer‐binding protein XylR: a structural model of its N‐terminal domain

Abstract: The prokaryotic enhancer-binding protein XylR is the central regulator of the toluene degradation pathway in Pseudomonas species. Copious genetic and biochemical data indicate that the N-terminal domain of the protein (domain A) interacts directly with m-xylene, which renders the protein competent as a transcriptional activator. Single-site and shuffling mutants of XylR or homologues have been reported to change or expand their effector profiles. Here, we follow a fold recognition approach to generate three-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 50 publications
1
58
0
Order By: Relevance
“…Genetic and biochemical data indicate that the N-terminal domain of the protein interacts directly with m-xylene, which renders the protein competent as a transcriptional activator. Three-dimensional models that go some way to explaining the molecular basis for interaction with substrate have been generated for the V4R domains of XylR and DmpR (17).…”
Section: Ebps Containing V4r Domainsmentioning
confidence: 99%
“…Genetic and biochemical data indicate that the N-terminal domain of the protein interacts directly with m-xylene, which renders the protein competent as a transcriptional activator. Three-dimensional models that go some way to explaining the molecular basis for interaction with substrate have been generated for the V4R domains of XylR and DmpR (17).…”
Section: Ebps Containing V4r Domainsmentioning
confidence: 99%
“…Attempts to obtain direct structural information on the proteins of this subclass have been frustrated by the difficulty to purify and stabilize the full protein. Nevertheless, a structural model for the XylR A-domain was proposed based on low but pertinent similarity to the A-chain of eukaryotic catechol O-methyl transferase [22]. This model, however, consists of only a single XylR A-domain protomer whereas the current hypothesis predicts that proteins from this class undergo an activation cycle of multimerization and multimer disassembly [23].…”
Section: Introductionmentioning
confidence: 94%
“…HbpR domains are depicted to scale according to the predictions by Jaspers et al [7]. (B) to (E) Fitting used swiss - model and was performed on XylR A-domain PDB coordinates as calculated by Devos et al [22]. (B) Ribbon model of HbpR A-domain residues 11–209, with predicted coils, alpha-helices and beta-sheets indicated.…”
Section: Introductionmentioning
confidence: 99%
“…The multimerized protein undergoes conformational changes producing a transcriptionally competent form of XylR (XylR a ) (Devos et al, 2002), which results in rapid transition between the active and inactive forms of the protein (Shingler, 2003). Comparing the expression used for Pr to the one presented in our previous work with the Pr/Ps system (Koutinas et al, 2010), the following minor differences can be identified.…”
mentioning
confidence: 99%